Adventure race's injuries - dos Santos, G.; Pastre, C. Marcelo [UNESP]; Amaral, Sandra Lia do [UNESP]; Monteiro, Henrique Luiz [UNESP] (Elsevier France-editions Scientifiques Medicales Elsevier, 2009)
Objective. - To describe the distribution of frequency of the injuries during adventure competition.Material and methods. - Fifty-five participants who underwent to the second stage of the Caloi Adventure Camp competition answered to a questionnaire about their personal characteristics, training status and injuries.Results. - The age of the athletes was 32 +/- 10 years old and the body mass index (BMI) 23.3 +/- 2.2 kg/m(2). The most frequent injuries occurred during trekking (61%), followed by mountain bike (24%). Abrasions (36.7%) and cuts (24.5%) were the most frequent injuries mentioned. Tissue level lesions occurred in 61.2% of the episodes. The most frequent injuries were contusions (16.3%) at muscular level, and sprain (6.1%) and fracture (6.1%) at osteoarticular system. Related to the body structure, the lower limb was the most affected (49%), mainly ankle (14.3%) and knee (12.2%). In the upper limb (30.6%), arm and forearm were more affected with cuts and abrasions. Neck and trunk were responsible for 20.4% of the injuries. Cramps (31%) and tendinitis (11%) were also mentioned.Conclusion. - The data suggest that it is necessary to create one training approach including prevention and logistics for participants rescue and rapid attendance during the tournament. (C) 2008 Published by Elsevier Masson SAS.
Keywords: Adventure race; Injuries